Adolescent Heavy Episodic Drinking: Neurocognitive Functioning during Early Abstinence. (11th February 2014) - Winward, Jennifer L.; Hanson, Karen L.; Bekman, Nicole M.; Tapert, Susan F.; Brown, Sandra A.
Abstract The present study investigated the rate and pattern of neuropsychological recovery in heavy episodic drinking teens during the initial days to weeks of abstinence from alcohol. Adolescents (ages, 16–18 years) with histories of heavy episodic drinking (HED; N = 39) and socio-demographically similar control teens (CON; N = 26) were recruited from San Diego area schools. HED and CON were comparable on 5th grade standardized math and language arts test performance to ensure similar functioning before onset of substance use. Participants were administered three neuropsychological test batteries with 2-week intervals during a 4-week monitored abstinence period. HED teens performed worse overall than CON on tests of prospective memory (p = .005), cognitive switching (p = .039), inhibition task accuracy (p = .001), verbal memory (p's < .045), visuospatial construction (p's < .043), and language and achievement (p's < .008). The statistically significant group × time interaction for block design demonstrated normalization within the 4 weeks of abstinence for the HED (p = .009). This study identified cognitive performance deficits associated with heavy episodic drinking in adolescence during early abstinence and with sustained 4-week abstention. These findings suggest alcohol-related influences on several underlying brain systems that may predate the onset of alcohol abuse or dependence or take longer than 4 weeks to recover. (JINS, 2014, 20, 218–229)